TANTANGAN PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI ERA REVOLUSI INDUSTRI 4.0 DI SMA NEGERI 5 PRABUMULIH - Karnegi, Dale; Iswahyudi, Iswahyudi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This paper has purpose to describe about education and readiness to answer the educational challenges of the 4.0 industrial revolution era in building information technology-based learning systems at Senior High School 5 Prabumulih. The readiness of Senior High School 5 Prabumulih in facing the challenges of education in the industrial revolution era 4.0 is by efforts to improve the abilities and students’ skills through information technology-based education in order to produce reliable graduates as a motor of progress in information technology-based national development to answer the challenges of Industry 4.0 which continues to accelerate.The current education management policy in Indonesia encourages all levels of education, especially at Senior High School Number 5 Prabumulih to take advantage of advances in the digital education technology of the revolutionary era 4.0.Some solutions that can be done include adjusting curriculum and policy in education, preparing human resources to utilize ICT, optimizing the ability of students, and developing the values (character) of students, as well as the readiness of digital-based learning facilities and infrastructure.